Baronniesia delioti gen. n. sp. n., a new subterranean Leptodirini from the French Pyrenees (Coleoptera: Leiodidae: Cholevinae) - Fresneda, Javier; Bourdeau, Charles; Faille, Arnaud (Zootaxa, 2009)
Baronniesia delioti Fresneda, Bourdeau & Faille gen. n. & sp. n., tribe Leptodirini (Coleoptera, Leiodidae, Cholevinae), is described from the French central Pyrenees (Hautes-Pyrénées, Esparros, subterranean river of Artigaléou-Arodets). The genus is remarkable for the large body size and the strong sexual dimorphism in antennae of its type species. The structure of the aedeagus and the inner sac, with two additional strongly curved feather-like structures, forming an inverted “V”, and the lateral styles with only three spines without other structures, indicates affinities between the new genus and the Antrocharis group, diversified in the eastern part of the Pyrenean range. The limestone area in the central Pyrenees where this new genus was discovered appears to be a contact area between the eastern and western faunas of the Pyrenean cave beetles, both for Leiodidae: Leptodirini and Carabidae: Trechini.